Porcine cGAS-STING signaling induced autophagy inhibits STING downstream IFN and apoptosis - Xia, Nengwen; Zheng, Wanglong; Jiang, Sen; Cao, Qi; Luo, Jia; Zhang, Jiajia; Xu, Yulin; Sun, Shaohua; Zhang, Kaili; Chen, Nanhua; Meurens, François; Zhu, Jianzhong (Frontiers in Immunology, 2022)
The innate immune DNA sensing cGAS-STING signaling pathway has been widely recognized for inducing interferons (IFNs) and subsequent antiviral state. In addition to IFN, the cGAS-STING pathway also elicits other cell autonomous immunity events including autophagy and apoptosis. However, the downstream signaling events of this DNA sensing pathway in livestock have not been well defined. Here, we systematically analyzed the porcine STING (pSTING) induced IFN, autophagy and apoptosis, revealed the distinct dynamics of three STING downstream events, and established the IFN independent inductions of autophagy and apoptosis. Further, we investigated the regulation of autophagy on pSTING induced IFN and apoptosis. Following TBK1-IRF3-IFN activation, STING induced Atg5/Atg16L1 dependent autophagy through LIR motifs. In turn, the autophagy promoted the pSTING degradation, inhibited both IFN production and apoptosis, and thus restored the cell homeostasis. Therefore, this study sheds lights on the molecular mechanisms of innate immunity in pigs.